SKRINING FITOKIMIA DAN ANALISIS KROMATOGRAFI LAPIS TIPIS EKSTRAK KULIT PISANG KEPOK - Isna Mulyani; Rizki Nisfi Ramdhini; Syaikhul Aziz (JFL : Jurnal Farmasi Lampung, 2021)
Kepok banana peel is an organic waste that has potential to be reused. Several studies proofed that banana peels have antioxidant activity, antimicrobial, inhibit the formation of cholesterol crystals and gallstones, diuretic effect, and mutagenic effect. This study aims to identify secondary metabolites contained in kepok banana peels using qualitative test methods (phytochemical screening) and thin layer chromatography analysis. The results of the phytochemical screening of kepok banana peel indicated the presence of alkaloids, monoterpenes/sesquiterpenes, phenols/tannins, saponins,and quinones. Thin layer chromatographic profile of ethanol extract showed the presence of flavonoid, phenol, and quinone compounds.Keywords: Phytochemical, chromatography, banana peel